Criminal Law Analysis of The Role of Influencers in Online Gambling Promotion in Indonesia - Muhamad Ilham; Sumarno Sumarno; Ismaidar Ismaidar (CV. Era Digital Nusantara, 2026)
The phenomenon of online gambling in Indonesia involving influencers as promoters through social media raises complex criminal law issues. This normative research with a statutory approach analyzes legal regulations and criminal liability of influencers in online gambling promotion. The results indicate that this practice is regulated through Article 27 paragraph (2) in conjunction with Article 45 paragraph (3) of the ITE Law No. 1/2024 with a maximum criminal threat of 10 years and/or a fine of IDR 10 billion, Article 426 of Law No. 1 of 2023 concerning the Criminal Code with a maximum imprisonment of 9 years or a category VI fine, as well as the Consumer Protection Law. Criminal liability requires accountability capacity, intent, and absence of justification reasons, accompanied by consequences in the form of criminal sanctions, asset seizure, and social media account blocking.